Contextualization of Mahmud Yunus' Concept of Islamic Education in Madrasah Tsanawiyah - Rimayul Wafa; M. Yunus Abu Bakar; Ah. Zakki Fuad (State Islamic Institute of Madura, 2025)
Islamic education evolves to respond to global changes. This situation is a challenge for Islamic education to ensure its progress in terms of existence and management. This study aims to determine the implementation of Mahmud Yunus' concept of Islamic education in MTs. Manba'ul Hikam Sidoarjo. The method used in this research is descriptive method with qualitative approach. Data collection is done by using observation, interview and documentation methods. Data analysis is done through data reduction, data interpretation, and conclusion. The results of this study indicate that Mahmud Yunus' concept of Islamic education can be implemented to overcome the problems of Islamic education at MTs. Manba'ul Hikam Sidoarjo. In MTs. Manba'ul Hikam Sidoarjo, Mahmud Yunus' concept of Islamic education is implemented starting from the objectives of Islamic education based on moral education, an integrated curriculum, methods that are always developing, educators who must be willing to learn with technological developments and evaluations that use letters instead of numbers. Unlike previous studies that primarily explored Mahmud Yunus’s ideas in a historical or theoretical context, this research provides an empirical application within a contemporary madrasah setting, offering a practical framework for integrating classical Islamic educational thought with modern curriculum policies.